2018
DOI: 10.1152/ajpheart.00742.2017
|View full text |Cite
|
Sign up to set email alerts
|

Role of endothelial microRNA-23 clusters in angiogenesis in vivo

Abstract: The capillary network is distributed throughout the body, and its reconstruction is induced under various pathophysiological conditions. MicroRNAs are small noncoding RNAs that regulate gene expression via posttranscriptional mechanisms and are involved in many biological functions, including angiogenesis. Previous studies have shown that each microRNA of miR-23 clusters, composed of the miR-23a cluster (miR-23a~27a~24-2) and miR-23b cluster (miR-23b~27b~24-1), regulates angiogenesis in vitro. However, the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…The following primers were used for real-time PCR: Dicer, 5′-CACACGCCTCCTACCACTACAACAC-3′ and 5′-CCGTGGGTCTTCATAAAGGT-3′; glyceraldehyde 3-phosphate dehydrogenase (GAPDH), 5′-AAATGGTGAAGGTCGGTGTG-3′ and 5′-TGAAGGGGTCGTTGATGG-3′. For the real-time PCR analysis of mature miRNA expression, the TaqMan ® MicroRNA Reverse Transcription Kit and TaqMan ® MicroRNA Assays (Applied Biosystems, Foster City, CA, USA) were used, according to the manufacturer’s protocols [38,39].…”
Section: Methodsmentioning
confidence: 99%
“…The following primers were used for real-time PCR: Dicer, 5′-CACACGCCTCCTACCACTACAACAC-3′ and 5′-CCGTGGGTCTTCATAAAGGT-3′; glyceraldehyde 3-phosphate dehydrogenase (GAPDH), 5′-AAATGGTGAAGGTCGGTGTG-3′ and 5′-TGAAGGGGTCGTTGATGG-3′. For the real-time PCR analysis of mature miRNA expression, the TaqMan ® MicroRNA Reverse Transcription Kit and TaqMan ® MicroRNA Assays (Applied Biosystems, Foster City, CA, USA) were used, according to the manufacturer’s protocols [38,39].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that many miRNAs regulate the angiogenesis in vitro and in vivo. The miR-23 has demonstrated to be dispensable for embryonic development and angiogenesis in vivo and in vitro [29]. miR-616-3p promotes angiogenesis and EMT in gastric cancer [30].…”
Section: Introductionmentioning
confidence: 99%
“…Some miRNAs have emerged as key players in angiogenesis. These angiogenesis-related miRNAs are abundant in the vascular system and are involved in regulation of endothelial function and angiogenesis [ 17 , 18 , 19 ]. The representative miRNAs include miR-126, miR-221/222, the miR-23~27~24 cluster, and the miR-17~92 cluster [ 20 ].…”
Section: Introductionmentioning
confidence: 99%